2016
DOI: 10.1001/jamasurg.2016.2733
|View full text |Cite
|
Sign up to set email alerts
|

Combined Epidural-General Anesthesia vs General Anesthesia Alone for Elective Abdominal Aortic Aneurysm Repair

Abstract: Combined EA-GA was associated with improved survival and significantly lower HRs and ORs for mortality and morbidity in patients undergoing elective AAA repair. The survival benefit may be attributable to reduced immediate postoperative adverse events. Based on these findings, EA-GA should be strongly considered in suitable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 23 publications
2
21
0
3
Order By: Relevance
“…11,12 Recent retrospective data suggest that, in abdominal aortic surgery, the addition of an epidural to GA improves the 5 yr survival compared to GA alone. 15 The risk of GA varies directly with American Society of Anesthesiologists physical status, but there is no clear evidence that using RA in high-risk patients influences outcome. 16 PNB avoids the haemodynamic compromise of CNB, and theoretically may be safer than CNB or GA in high-risk patients, but there is only anecdotal evidence to support this, albeit as experts PNB would be our choice.…”
Section: Mortalitymentioning
confidence: 99%
“…11,12 Recent retrospective data suggest that, in abdominal aortic surgery, the addition of an epidural to GA improves the 5 yr survival compared to GA alone. 15 The risk of GA varies directly with American Society of Anesthesiologists physical status, but there is no clear evidence that using RA in high-risk patients influences outcome. 16 PNB avoids the haemodynamic compromise of CNB, and theoretically may be safer than CNB or GA in high-risk patients, but there is only anecdotal evidence to support this, albeit as experts PNB would be our choice.…”
Section: Mortalitymentioning
confidence: 99%
“…7,20e22 Recently, Bardia et al have suggested that combined epidural with GA vs. GA alone was associated with significantly lower mortality and morbidity in patients undergoing elective abdominal aneurysm open repair. 6,23 However, TAAA surgery is more complex and presents unique features which may account for the different results observed. Furthermore, the present data concerning the incidence of neurological complications are encouraging, as no case of epidural haematoma was recorded in a context in which patients require systemic intra-operative heparinisation and are at high risk of developing peri-operative coagulopathy secondary to massive bleeding and need for transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…EA also improved outcomes after major surgery, 4,5 including open abdominal aortic aneurysm (AAA) repair. 6 Compared to AAA repairs, TAAA surgery is a longer and more complex intervention, with a higher risk of complications due to major involvement of the cardiovascular and pulmonary systems. Left thoracotomy is associated with both greater pain and pulmonary complications than AAA.…”
Section: Introductionmentioning
confidence: 99%
“…Eine aktuelle Cochrane-Analyse beschreibt eine Reduktion der Häufigkeit von postoperativen Myokardinfarkten, von respiratorischen Komplikationen, gastrointestinalen Blutungen und der Schmerzintensität [11]. In einer retrospektiven Analyse von mehr als 1500 BAA-Operationen konnte eine Abnahme von respiratorischen Komplikationen, dialysepflichtigem Nierenversagen, Darmischämien und Re-Operationen beobachtet werden [12].…”
Section: Gefäßchirurgieunclassified